CT criteria for Differentiation between True and False Lumen in Aortic Dissection - Siriapisith, Thanongchai; Tongdee, Trongtum; Tongdee, Ranista; Jitnuson, Poonsook; Karuvanarint, Supavadee (Siriraj Medical Journal, 2004)
Acute aortic dissection can be an emergency event characterized by the splitting of tunica media of the aortic wall by high pressure arterial blood throught an intimomedial tear: The CT imaging is a currently emerging technique for dianosis and evaluation of aortic dissection and has sensitivity and specificity of nearly 100%. The differentiation between true and false lumens of aortic dissection is important for percutaneous treatment with endovascular grafts or surgical repair: Previous studies described CT criteria to distinguish true from false lumens. The most reliable sings in this study are outer wall calcification, intraluminal thrombus, eccentric flap calcification, a larger area at one-quarter distance, and a larger area at one-half distance.